Sistem Penunjang Keputusan (SPK) Pemilihan Supplier Terbaik Dengan Metode MOORA - Haris Andri, Rizkhan; Permana Sitanggang, Doni (Riset Sinergi Indonesia (RISINDO), 2023)
In a company that the selection of the right supplier is an important factor in the success of a company. In the cement industry, selecting the right supplier can affect the quality of raw materials and ultimately affect the quality of the final product. Therefore, the Semen Padang company needs to select suppliers carefully and based on clear criteria. The MOORA (Multi-Objective Optimization by Ratio Analysis) method is a decision-making method that can be used to assist the Semen Padang company in choosing the best supplier. This method can be used to select suppliers based on certain criteria and assign a weight value to each criterion. In the MOORA method, this weight value is used to rank each supplier tested By implementing the MOORA method at Semen Padang companies, it is hoped that the company will be able to select suppliers more efficiently and accurately. This method can help companies evaluate supplier selection criteria and choose the supplier that best suits their needs. Thus, it can improve the quality of the final product and help Semen Padang companies achieve their business goals. Software or program, which is a set of instructions that allows hardware to be able to process data. UML is a standard language based on diagrams or drawings that aims to visualize, define and build models. Use Case Diagrams, Class Diagrams, Sequence Diagrams, and Activity Diagrams. PHP is a programming language used to translate program code base into machine code that can be understood by computers by adding HTML. PHP is known as a scripting language, which integrates with HTML tags, is executed on the server, and is used to create dynamic web pages such as Active Server Pages or Java Server Pages. PHP Hypertext Preprocessor is a multifunctional open source script that is very suitable for developing a website.